Control of Reversible Degradation Mechanisms in Fuel Cells: Mitigation of CO contamination. Issue 7 (2016) - Tjønnås, Johannes; Zenith, Federico; Halvorsen, Ivar J.; Klages, Merle; Scholta, Joachim
Abstract: Fuel Cells are subject to several degradation phenomena where some are reversible and some irreversible. Normally all contribute to a reduced cell voltage, but it may be complicated to discriminate the particular causes. A brief overview is given and a method for modelling and controlling the particular case of CO contamination by use of active and adaptive air-bleed manipulation is presented.